Escuelas de artes oficios y reintegración (2021)
Historically, Colombia has been a country immersed in an armed conflict, caused mainly by drug trafficking, between different participants, such as illegal armed groups and the State. Generating a problematic reality of inequality, massacres, land dispossession, recruitment of minors, forced disappearances, planting and production of coca, terrorism, paramilitarism, among others. That is why this project aims to mitigate the pain of the victims, contributing to the reconstruction of the truth and the dissemination of the historical memory of the conflict; in a participatory manner between the victims, the community and the State. Through the treatment, learning and accompaniment of ancestral traditions and arts, in different cultural settings and practical knowledge, developed in a space with characteristic elements. Generating equipment with its own sensations in the municipality of Antioquia in the city of Medellín.